IMPLEMENTASI KEGIATAN JUMAT BERBAGI DALAM MENANAMKAN AKHLAK MULIA PADA ANAK USIA DINI - Alfia Fayruz; Nur Aini Zaida (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2024)
The formation of noble morals is a crucial element in the early childhood education process. Moral education in Islam is closely related to the characteristics of the prophet. The recommendation to emulate the noble character of Rasulullah SAW is contained in the Word of Allah Surah Al-Ahzab (33): 21. In terms of noble moral education, RA Labschool IIQ Jakarta is holding a Friday sharing activity program to instill noble morals in early childhood which is guided by the example of Rasulullah. The main objective of this research is to determine the implementation of Friday sharing activities in instilling noble morals in young children, especially 5-6 years old. This research uses qualitative methods with descriptive research type. The place of research was carried out at RA Labschool IIQ Jakarta. The subjects of this research were the school principal, 4 teachers, and 10 parents of RA Labschool IIQ Jakarta. The data collection techniques used were observation of Friday sharing activities at RA Labschool IIQ Jakarta, interviews, and documentation. Next, the data analysis techniques used are data collection, data reduction, and data conclusions. The results of this research show that Friday sharing activities have instilled the 4 noble qualities of the Prophet, namely Shiddiq, amanah, tabligh, fathanah at an early age aged 5-6 years at RA Labschool IIQ Jakarta by implementing the methods of example, habituation, advice, attention and supervision, and punishment.